Emotional intelligence, social competence in adolescents with mobility disabilities within a stress-resilience model - Karaffová, E. (Eva) (2012)
To examine the influences from life stress and the hypothesized protective variables of social competence, emotional intelligence on quality of life in adolescents with mobility disabilities within a stress–resilience model. Variables were assessed with questionnaires completed by 89 adolescents with a mobility disability and healthy individuals (aged 11–15 years). Data was collected with The Child and Youth Resilience Measure, Trait EI Questionnaire and Tromso Social Intelligence Scale. Meaning and contribution of this study is seen in the identification of running and successful strategies and resources of resilience can show the ways how to improve the quality of life and the feeling of personal contentment in situations that are strenuous for a man.